Placement of a triple‐layered covered versus uncovered metallic stent for palliation of malignant gastric outlet obstruction: A multicenter randomized trial. Issue 2 (29th April 2013) - Maetani, Iruru; Mizumoto, Yoshinori; Shigoka, Hiroaki; Omuta, Shigefumi; Saito, Michihiro; Tokuhisa, Junya; Morizane, Toshio
<x xml:space="preserve">Abstract</x> Background Usually, uncovered self‐expandable metallic stents (SEMS) are used for palliation of malignant gastric outlet obstruction (GOO). A triple‐layered covered SEMS is reported to be efficacious, but its performance has not been compared with uncovered SEMS. The present study is the first to compare the efficacy and safety of a triple‐layered covered versus uncovered SEMS. Patients and Methods A multicenter randomized study was conducted in two tertiary referral centers, with 62 eligible patients with symptomatic GOO to receive covered (n = 31) or uncovered SEMS (n = 31). The primary endpoint was SEMS patency, and secondary endpoints were success rate and adverse events after complete follow up. Results Both groups had a technical success rate of 100% and comparable clinical success rates (P = 0.67). There was nostatistically significant difference in stent patency and adverse events between the two groups (P = 0.52 and P = 0.38, respectively). Although the occurrence rate of persistent obstructive symptoms was comparable (P = 0.42), that of recurrent obstructive symptoms was higher in the uncovered group (29% vs 3.6%, P = 0.0125). Patient survival did not differ between groups (P = 0.34). Conclusion There was no statistically significant difference in stent patency, but use of a triple‐layered covered SEMS was associated with less frequent stent dysfunction more than 4 weeks after stenting, despite similar short‐term outcomes.